Molecular characterisation of Mycoplasma gallisepticum genotypes from chickens in Zimbabwe and South Africa - Moretti, Serena A.; Boucher, Charlotte E.; Bragg, Robert R. (South African Journal of Science, 2013)
Mycoplasma gallisepticum is an economically important pathogen of poultry worldwide. Yet the characterisation of M. gallisepticum field strains present in southern Africa has not previously been reported. We characterised various M. gallisepticum genotypes within the region and highlight the unique differences between two genotypes found in South Africa and Zimbabwe. PCR targeting a partial region of the mgc2 gene was used to screen various poultry farms in South Africa and Zimbabwe for M. gallisepticum. Samples were characterised using multilocus gene-targeted sequencing. Portions of the surface protein encoding pvpA, gapA and mgc2 genes and the uncharacterised surface lipoprotein gene designated MGA_0319 were sequenced and analysed. Nucleotide sequences were compared to vaccine and reference strains as well as to strains from different countries. The South African genotype contained unique mgc2 and pvpA gene regions, while the Zimbabwean genotype proved to be even more distinct with unique gapA, mgc2 and pvpA gene regions. In addition, BLAST results showed high similarities in the partial mgc2 gene region between the South African and Zimbabwean genotypes and the ‘atypical’ Israeli RV-2 strain, suggesting a link in its epidemiology. These results also allow for improved control strategies for southern Africa, and the use of more effective vaccine strains.